Acromegaly and Colorectal Neoplasm: An Update - Kasuki, Leandro; Maia, Bernardo; Gadelha, Mônica R. (Frontiers in Endocrinology, 2022)
Acromegaly is a systemic disease caused by excessive inappropriate secretion of GH and IGF-I levels, resulting in many systemic complications, including cardiovascular, respiratory, metabolic diseases, and a possible increased risk of some neoplasias. Although many studies on acromegaly and cancer remain uncertain, most data indicate that colorectal cancer (CRC) incidence is increased in this population. The exact mechanism involved in the role of GH-IGF-I axis in CRC has not been fully explained, yet it is associated with local and circulating effects of GH and IGF-I on the colon, promoting angiogenesis, cell proliferation, risk of mutation, inhibition of tumor-suppressor genes and apoptosis, thus facilitating a tumor microenvironment. Nevertheless, population-based studies present controversial findings on CRC incidence and mortality. All worldwide guidelines and expert consensuses agree with the need for colonoscopic screening and surveillance in acromegaly, although there is no consensus regarding the best period to do this. This review aims to analyze the existing data on CRC and acromegaly, exploring its pathophysiology, epidemiological studies and their limitations, colonic polyp characteristics, overall cancer and CRC incidences and mortality, risk factors for colon cancer pathophysiology, and recommendation guideline aspects.